Addiction and technology: Plus ça change plus c’est la même (The more things change, the more they remain the same) - Sarin, Alok (Indian J Psychiatry, 2017)
Excessive use of the internet for gambling, gaming and behavioural addiction, are a focus of contemporary interest. The authors delve into the archives to explore the connections between the growth of various forms of technology, commerce, addictive behaviours and responses of the State, in colonial India. The interplay between the growth of the telegraph network in 19th century India, and its influence on various forms of gambling, including speculation on opium prices, and the rain, as a theme of wager make interesting stories, as do the governmental responses to these. Clinical and social responses to information technology raised much the same concerns as they do now